PENGEMBANGAN E-LKPD BERBASIS ETNOMATEMATIKA PADA MATERI TRANSFORMASI GEOMETRI - Febrianti, Ina; Rihatul Hima, Lina; Santia, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an Ethnomathematics-Based Electronic Student Worksheet (E-LKPD) using the Simpang Lima Gumul (SLG) Monument context on geometric transformation material that is valid and practical for use with 11th-grade senior high school students. This research uses the Research and Development (R&D) method with the ADDIE development model; however, this article focuses on the Analysis, Design, Development stages, along with the validity and practicality results. Validation was conducted by content experts, media experts, and educational practitioners, while the practicality test was carried out through a limited trial involving 10 students. Practitioner validation obtained 88% (very valid), content expert validation reached 87% (very valid), and media expert validation reached 85% (very valid). The limited trial showed an average student response of 83.6% (very good). Therefore, the ethnomathematics-based E-LKPD using the SLG Monument is declared valid and practical as a mathematics learning medium for geometric transformation material for 11th-grade senior high school students.